BS EN ISO 16486-3. Plastics piping systems for the supply of gaseous fuels. Unplasticized polyamide (PA-U) piping systems with fusion jointing and mechanical jointing. Part 3. Fittings (28th October 2019) - British Standards Institution,
No abstract available